Gestão Ambiental dos Resíduos Sólidos: análise do financiamento para o setor de resíduos sólidos do município de Macapá/AP - PORTO, Juliana Alves Lima (Universidade Federal do Pará, 2019)
In Brazil, the responsibility for the management of solid waste is the municipal public power, which has a limited budget that does not meet the real need foreseen in law regarding their environmental management. In this master's dissertation, the analysis of public policy financing and its importance for the environmental management of solid wastes in the municipality of Macapá / AP, from the period of 2012 to 2015, was analyzed. Public environmental management of solid wastes was also evaluated; with information on fundraising of federal voluntary transfers to this sector; and proposing measures and actions to improve fundraising. In order to reach the objectives, it was established as a methodological procedure for the descriptive and exploratory objectives, and for the technical - bibliographic and documentary procedures, being applied in nature. Interviews were conducted with managers of the solid waste sector who demonstrated the main deficiencies and challenges of solid waste management in Macapá, as well as raising the financial deficit of the sector, as well as proposing federal funding through the Thematic Program of the PPA / federal Solid Waste and incentive to the composting and selective collection program. Finally, among the proposed measures, the urgent need for approval of the Municipal Sanitation Basic Plan and consequently Solid Waste